Trade liberalization and labor market in developing countries: Theory and evidence - Jorge Saba Arbache (University of Kent, Department of Economics, 2001)
This paper presents a review of the theoretical and empirical literature on the effects of trade liberalization on the labor markets of developing countries. We discuss models which seek to explain the empirical finding that openness has increased wage inequality in several developing countries.
Keywords: J3; J6; F16; D33; O15; 330; trade liberalization; technology; wages; employment; income distribution; developing countries; Außenhandelsliberalisierung; Einkommensverteilung; Arbeitsmarkt; Entwicklungsländer